Tetragonal layered compounds with vanadyl phosphate structure and their intercalation reactions - Beneš, Ludvík; Zima, Vítězslav (Univerzita Pardubice, 1996)
Intercalation reactions of vanadyl phosphate, niobyl phosphate, vanadyl arsenate, and vanadyl sulphate are summarized. In the review, the intercalations of molecular guests (water, alcohols, amines, carboxylic acids, amides, heterocycles, and metallocenes) and ions (alkali metals, divalent metals, and alkylammonium ions) are described. Layered compounds derived from vanadyl phosphate dihydrate, in which a part of vanadyl group is replaced by trivalent metal (Al, Cr, Fe, Ga, Mn), are mentioned.